FAKTOR UTAMA SWASEMBADA PANGAN TINGKAT RUMAH TANGGA PETANI LAHAN KERING DI KABUPATEN WONOGIRI PROVINSI JAWA TENGAH - DARSONO DARSONO (Universitas Sebelas Maret, 2012)
The dynamics of food sufficiencies for the most vulnerable households are in the dryland farm households. This study aims to determine the food sufficiency situation at household level include the status and major factors. Using primary and secondary in Wonogiri compiled panel data were analyzed by linear regression models at both the region and household. The results show that, dryland farmer households in Wonogiri have good food suficiency characterized by a surplus of rice (level of consumption per capita/year below the national figure of 97.1 kg).